Age At Menarche and Factors Associated Among Girls of a Primary Health Centre Area in Davangere, India - Mane, Kusum S; Sharankumar, Holyachi; Bheemayya, Badesab (National Journal of Community Medicine, 2016)
Background: The age at menarche is a developmental milestone, which is highly variable and highly sensitive to a variety of internal and external forces. Knowledge of the age at menarche will help the government to design and implement programmes about reproductive health of women, to set laws about age at marriage, family planning, etc and to decide the appropriate age at which the topics like the sex education, contraception and sanitary practices can be incorporated in schools. Methods: This observational cross sectional study was conducted among school going adolescent girls aged between 10 and 16 years. 246 girls participated in the study and predesigned questionnaire was administered. Results: Out of 246 cases studied 152 cases were having menstruation, most frequent age of menarche being 12 years when 46 cases (18.7%) had its onset. Mean age at menarche was found to be12.14 (± 1.086). There seems to be definite association of various factors which modify the age at menarche like mother’s menarcheal age, socio-economic status. Conclusion: There was a positive correlation between menarche and maternal age at menarche and socioeconomic status.